2022
DOI: 10.1073/pnas.2205767119
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of emotions and the prominence of positivity in #BlackLivesMatter tweets

Abstract: Emotions are a central driving force of activism; they motivate participation in movements and encourage sustained involvement. We use natural language processing techniques to analyze emotions expressed or solicited in tweets about 2020 Black Lives Matter protests. Traditional off-the-shelf emotion analysis tools often fail to generalize to new datasets and are unable to adapt to how social movements can raise new ideas and perspectives in short time spans. Instead, we use a few-shot domain adaptation approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…It encourages participation in any movements and sustained involvement within them. A study conducted by Field et al [20], adopted natural language processing techniques to analyze emotions conveyed in tweets about the 2020 black lives matter protests. In their study, a few-shot domain adaptation approach was used to measure the different emotions expressed in the tweets following the death of George Floyd in May 2020.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It encourages participation in any movements and sustained involvement within them. A study conducted by Field et al [20], adopted natural language processing techniques to analyze emotions conveyed in tweets about the 2020 black lives matter protests. In their study, a few-shot domain adaptation approach was used to measure the different emotions expressed in the tweets following the death of George Floyd in May 2020.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, the explosive growth of a movement dedicated to racial equality, which, by some accounts, was possibly the largest protest movement in American history (Buchanan, Bui and Patel, 2020), likely posed a perceived threat to and induced fear and anxiety in many white Americans (Rose, 2020;Smith and King, 2021;Field et al, 2022). Second, the unexpected outbreak of large-scale protests created substantial spatial and temporal variation in the incidence of BLM protests, and therefore a source of variation in perceived racial threats.…”
Section: Introductionmentioning
confidence: 99%
“…Research that has examined geographic state and city-level correlations between BLM tweets and protest activity in 2020 further supports the predictions of the present research. That is, such research has found that BLM tweets are associated with negative emotions like anger yet also positive emotions like hope and optimism ( 13 ). Thus, the present research builds on such findings in several ways.…”
Section: Introductionmentioning
confidence: 99%